Impact of dam flushing operations on sediment dynamics and quality in the upper Rhône River, France. (1st February 2020) - Lepage, Hugo; Launay, Marina; Le Coz, Jérôme; Angot, Hélène; Miège, Cécile; Gairoard, Stéphanie; Radakovitch, Olivier; Coquery, Marina
Abstract: The Rhône River (France) has been used for energy production for decades and 21 dams have been built. To avoid problems due to sediment storage, dam flushing operations are periodically organized. The impacts of such operations on suspended particulate matter (SPM) dynamics (resuspension and fluxes) and quality (physico-chemical characteristics and contamination), were investigated during a flushing operation performed in June 2012 on 3 major dams from the Upper Rhône River. The concentrations of major hydrophobic organic contaminants (polychlorinated biphenyls, polycyclic aromatic hydrocarbons - PAHs, bis(2-ethylhexyl)phthalate [DEHP] and 4-n-nonylphenol), trace metal elements, particulate organic carbon (POC) and particle size distribution were measured on SPM samples collected during this event as well as on those obtained from 2011 to 2016 at a permanent monitoring station (150 km downstream). This allows to compare the SPM and contaminant concentrations and fluxes during the 2012 dam flushing operations with those during flood events and baseflow regime. At equal water discharge, mean SPM concentrations during flushing were on average 6–8 times higher than during flood events recorded from 2011 to 2016. While of short duration (19 days), the flushing operations led to the resuspension of SPM and contributed to a third of the mean annual SPM flux. The SPM contamination was generally lower during flushing than during baseflow or flood, probably due to the fact that flushing transports SPM only issued from resuspended sediment, with no autochtonous particles nor eroded soil. The only exception are PAHs and DEHP with higher concentrations during flushing, which must be issued from the resuspension of legacy-contaminated sediments stored behind the dams before the implementation of emission regulations. During flushing, the variations of POC and contaminant concentrations are also mostly driven by particle size. Finally, we propose a list of recommendations for the design of an adequate monitoring network to evaluate the impact of dam flushing operations on large river systems. Graphical abstract: Image 1 Highlights: Dam flushing operations were monitored on the Upper Rhône River (France). Sediment dynamic differed during flushing operations and flood events. About 0.6 Mt of SPM were stored in the Upper Rhône from 2011 to 2016. 21–37% of the mean annual SPM flux transited during the 2012 flushing operations. Particulate contaminant concentrations were driven by particle size and SPM origin.